Income-based price subsidies, parallel imports and markets access to new drugs for the poor - Rajat Acharyya; María D. C. García-Alonso (University of Kent, Department of Economics, 2008)
In health markets, government policies tend to subsidize poorer groups. The purpose of this paper is to analyze the implications of an income-based subsidy policy on the incentives of countries to implement price arbitrage and of firms to provide market access to poorer groups.
Keywords: D4; L1; I1; 330; pharmaceuticals; income based subsidies; parallel imports; market access; Gesundheitswesen; Pharmazeutisches Produkt; Gesundheitskosten; Niedrigeinkommen; Öffentlicher Transfer; Preisdifferenzierung; Theorie